Perancangan E-Board Sebagai Alat Distribusi Informasi Pada Sistem Kerja Sama Asinkron Tersebar - Yosanny, Agustinna; Prasetio, Yen Lina; Lasiman, Irwan; Welly, Welly (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The design of e-Board was undertaken to meet the necessary of information between colleagues that nowadays has become more essential and vital especially in a team work that applying distributed asynchronous co-operative work system. In which, members of the team are distributed in time and space; therefore information should be well distributed to support the cooperative work between them. The research was applying analysis and design methodology. The analysis methodology was undertaken through literature study, current system observation, questionnaire survey to users to identify characteristics of the current and entailed information distribution media. The design methodology was undertaken through database, features, system, and screen layout design. Results of the research found that the information distribution media for team work which has applied distributed asynchronous co-operative work system should have the ability of private access for each member, better organization in information categorizing, structured information for task assignment, and supporting member's mobility. In conclusion, the application has been expected to help task assignment, distribution and organization of information in the distributed asynchronous co-operative work system to be easier and simpler.